Tensile, Bending Testing on Straw Fiber Composites 00 and 900 Angle Orientations with Polyester Matrix - Gundara, Gugun; Nifal Nugraha; Wagiman, Acep (Jurnal Multidisiplin Madani, 2024)
Currently, the development of science and technology continues to develop in all fields, such as vehicle construction, building construction, industry, and also the field of materials engineering, especially composites. Composite materials generally consist of two elements, namely fibers as a filler and a binding material for these fibers which is called a matrix. In composites, the main element is fiber, while the binding material uses polymer material which is easy to form and has high binding power. The aim of this research is to determine the effect of straw fiber length oriented at 0° and 90° angles in polyester matrix composites on tensile and bending strength. The influence of straw fiber length provides a value for maximum tensile strength with a value of 28.604 Mpa with a fiber length of 15 mm and an angle of 0°. Meanwhile, the angle direction of 900 has a greater value at a fiber length of 10 mm, amounting to 19.619 MPa. The influence of straw fiber length provides a value for maximum bending strength with a value of 86.29 MPa with a fiber length of 10 mm and an angle of 0°. Meanwhile, the maximum tensile strength value at an angle of 900 with a fiber length of 15 mm is 40.02 MPa